SPEKULASI, PROYEKSI DAN INVESTASI DALAM ISLAM: MENCARI KESEIMBANGAN ANTARA RISIKO DAN KEUNTUNGAN - Narda Wati, Narda Wati; Rahmah, Nur Azizah; Iswanto, Bambang (LPPM University 17 Agustus 1945 Samarinda, 2024)
This article discusses the concepts of speculation, projection, and investment in Islam, as well as attempts to achieve a balance between risk and profit according to sharia principles. A deep understanding of financial risk, sustainable financial projections, and Islamic investment principles are the main focus. These concepts are applied in a practical context to show how individuals and institutions can take wise financial decisions taking into account Islamic ethical values. Through the merging of practical and theoretical approaches, this article provides a comprehensive view of how speculation, projection, and investment can be conducted in accordance with Islamic teachings. Speculation tends to involve an element of uncertainty and luck, which is contrary to the principles of justice and order in Islam. In Islam, speculative activities tend to be regarded as gambling involving a high element of uncertainty and ignorance. Investments in Islam must be halal, or not contrary to religious principles. Investments must also be made with due regard to the principles of fairness, transparency, and clear agreements.